Analisis Kinerja Keuangan UMKM Cak Wang Macro Indonesia - Teguh Gunawan Setyabudi (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to analyze the financial performance of PT Cak Wang Macro Indonesia. This company is engaged in the processing of coffee beans and the serving of ready-to-drink coffee and cafes. This research includes quantitative descriptive research. The research data is in the form of financial data consisting of assets, liquidity and equity. Financial can be obtained from the financial reports of PT Cak Wang Macro Indonesia. PT Cak Wang Macro Indonesia is located on Jalan Mastrip, Jember Regency, East Java Province. The company's financial performance is seen from the calculation of profitability ratios, liquidity ratios, leverage ratios, and activity ratios in one period. The results showed that through the calculation of profitability ratios it was known that the company's ability to generate profits, the calculation of the liquidity ratio was known to the company's ability to pay short-term debt, the calculation of leverage ratios was known to the company's ability to manage debt and the activity ratio was known to the effectiveness of inventory turnover and total assets of the company. Analysis of financial performance carried out can assist management in making business decisions.